Seasonal effect of dietary energy and protein level on the performance of growing guinea fowl (Numida meleagris) - MANDAL, A B; PATHAK, N N (The Indian Journal of Animal Sciences, 2014)
An experiments, with varying levels of dietary energy and protein, was conducted to assess the yield and chemical cumposition of meat of 3 varieties (pearl, lavender and while) of growing guinea fowl at 12 weeks of age. Nine dietary treatments combining 3 levels of protein and metabolizable energy (ME) in a factorial design were offered during each growth phase Le. 0-4,5-8 and 9-12 weeks of age. The levels of protein (%) were 24, 22 and 20-P1 : 22, 20 and 18-P2 and 20, 18 and 16-P3, respectively, with ME concentrations: 12.13 MJ (2800 keal) and -12.55 MJ (3000 k cal)-E1, 11.30 MJ (2700 k cal) and 11.72 MJ (2800 k cal) -E2-12 and, 10.46 (2500 k cal) and 10.88 MJ (2600 k calli kg-E), respectively, for the respective growth phases. After completion of 12 weeks of age, 30 birds (10 of each variety) were sacrificed to evaluate carcass traits and composition of thigh and breast muscles. The live weight at 12 weeks of age differed due to dietary levels of energy and protein. Live weights were higher (P